Deacidification type EVA film for solar cell and preparation method thereof

The EVA film for solar cells addresses acetic acid-induced degradation by incorporating a composite hydrotalcite acid remover and aminated anti-PID filler, achieving effective acid reduction and enhanced mechanical properties for improved solar module performance and lifespan.

CN119119905AActive Publication Date: 2024-12-13YANTAI HANSU CHEMICAL TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411641331.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2024-12-13
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

EVA films used in solar photovoltaic modules degrade due to acetic acid generation under high temperature and humidity, leading to reduced performance and shortened lifespan, with acetic acid accelerating photovoltaic module failure.

Method used

An EVA film for acid-removing solar cells is prepared using a composite hydrotalcite acid remover and an aminated anti-PID composite filler, enhancing acetic acid adsorption and mechanical properties through specific material formulations and processing steps.

Benefits of technology

The EVA film effectively reduces acetic acid content, improves mechanical properties, and enhances durability, resulting in improved power retention and extended module lifespan.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119905A_ABST
    Figure CN119119905A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of adhesive films, in particular to a deacidification type EVA film for solar cells and a preparation method of the deacidification type EVA film, and the deacidification type EVA film comprises the following raw materials: EVA resin, a main cross-linking agent, an auxiliary cross-linking agent, aminated anti-PID composite filler, a composite hydrotalcite deacidification agent, a lubricant, an ultraviolet light absorber, a light stabilizer, an antioxidant and a coupling agent. Phosphate ions are inserted between layers of magnesium-aluminum hydrotalcite, and nano titanium dioxide particles are loaded on the surface of the magnesium-aluminum hydrotalcite, so that the obtained composite hydrotalcite acid remover can effectively adsorb and capture acetic acid released from an EVA (Ethylene-Vinyl Acetate) film, and the purpose of effectively removing and inhibiting acid is achieved; through preparation and amination modification of the anti-PID composite filler, the obtained amination anti-PID composite filler can improve the mechanical property and the anti-PID capability of the EVA film, can capture free acetic acid in the EVA film and neutralize the free acetic acid into salt, further plays a role in deacidification, and improves the aging resistance of the EVA film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of adhesive film technology, and more specifically, to an EVA film for deacidified solar cells and its preparation method. Background Technology

[0002] Solar photovoltaic (PV) modules are currently the most common solar energy utilization devices, and their performance and lifespan are affected by the encapsulating film. EVA (ethylene-vinyl acetate copolymer) encapsulating film, as a key material in solar PV modules, is widely used in them due to its excellent light transmittance, weather resistance, and adhesion properties, for fixing and protecting solar cells. Since solar PV modules are exposed to complex external environments year-round, the EVA film must possess good weather resistance to ensure long-term stable operation. However, various problems exist in the market, such as the aging and failure of EVA film under high temperature and humidity conditions, leading to a decrease in PV module power and a shortened lifespan.

[0003] Furthermore, vinyl acetate in the EVA film can generate acetic acid when exposed to high-temperature and high-humidity outdoor environments or during the process temperatures of module manufacturing. When acetic acid is generated, the EVA film deteriorates and foams within the module, thereby reducing battery performance and shortening the overall module lifespan. Moreover, as the amount of freely moving acetic acid within the EVA film increases, the reaction between the freely moving acetic acid and the alkali precipitated on the glass surface accelerates, promoting the formation of sodium hydroxide (Na₂O₃). + The generation of freely movable Na + Under the influence of an applied electric field, the particles move towards the surface of the solar cell and accumulate in the antireflection layer, causing photovoltaic modules to face the problem of significant power degradation or even failure in a short period of time. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention provides an EVA film for acid-free solar cells and a method for preparing the same.

[0005] An EVA film for acid-removing solar cells, comprising, by weight, the following raw materials: 86–95 parts EVA resin, 1.8–4 parts main crosslinking agent, 0.1–0.5 parts co-crosslinking agent, 1.3–3.2 parts aminated anti-PID composite filler, 0.1–1.8 parts composite hydrotalcite deacidifying agent, 0.1–1.5 parts lubricant, 0.04–1 part ultraviolet absorber, 0.01–1 part light stabilizer, 0.1–1 part antioxidant, and 0.1–0.5 parts coupling agent; The raw materials for preparing the composite hydrotalcite acid remover include: 5-20 parts of phosphate-intercalated magnesium aluminum hydrotalcite, 1-14 parts of nano titanium dioxide particles, 10-30 parts of silane coupling agent KH-550 and 70-120 parts of ethanol solution with a mass fraction of 75%. The phosphate-intercalated magnesium aluminum hydrotalcite is a layered composite material formed by inserting phosphate ions between the layers of magnesium aluminum hydrotalcite. The raw materials for preparing the ammoniated anti-PID composite filler include: 1-12 parts of anti-PID composite filler, 100-160 parts of N,N-dimethylformamide, 20-45 parts of ethylenediamine, and 6-16 parts of ammonia water with a mass fraction of 30%. The raw materials for preparing the anti-PID composite filler include: surface-modified nano-tin oxide, silane coupling agent KH-550, and barium metaphosphate dispersion. The mass ratio of surface-modified nano-tin oxide, silane coupling agent KH-550, and barium metaphosphate dispersion is (1-6):(21-35):(90-130). The surface-modified nano-tin oxide is nano-tin oxide that has been modified with surfactant. The mass fraction of barium metaphosphate dispersion is 4-8%.

[0006] Furthermore, the VA content of the EVA resin is 28-33%, and the melt index is 25-43 g / 10 min.

[0007] Furthermore, the primary crosslinking agent is at least one of tert-butyl peroxycarbonate-2-ethylhexyl, tert-amyl peroxy(2-ethylhexyl)carbonate, tert-butyl peroxyacetate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxybenzoate, or dicumyl peroxide; the secondary crosslinking agent is at least one of triallyl isocyanurate, triallyl cyanurate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, propoxylated trimethylolpropane triacrylate, propoxylated neopentyl glycol diacrylate, or ethoxylated trimethylolpropane triacrylate; the lubricant is one or more of stearic acid, calcium stearate, zinc stearate, butyl stearate, stearamide, and oleamide; and the ultraviolet absorber is phenyl o-hydroxybenzoate, 2-(2'- The light stabilizer is at least one of the following: hydroxy-5'-methylphenyl)benzotriazole, 2,4-dihydroxybenzophenone, tris(1,2,2,6,6-pentamethylpiperidinyl)phosphite or 4-benzoyloxy-2,2,6,6-tetramethylpiperidine; the light stabilizer is at least one of bis-2,2,6,6-tetramethylpiperidinol sebacate, N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,6-hexanediamine, or 2,4-dichloro-6-(4-morpholinyl)-1,3,5-triazine; the coupling agent is at least one of silane coupling agent KH-570, silane coupling agent KH-560, silane coupling agent KH-670 or silane coupling agent KH-550; and the antioxidant is at least one of antioxidant 1010 or antioxidant 168.

[0008] A method for preparing an EVA film for an acid-removing solar cell includes the following steps: S1: Preparation of phosphate-intercalated magnesium aluminum hydrotalcite: Magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and phosphate were used as raw materials, sodium hydroxide was used as precipitant and deionized water was used as solvent. After solution preparation, titration co-precipitation, hydrothermal treatment, washing and drying, phosphate-intercalated magnesium aluminum hydrotalcite was obtained. S2: Preparation of composite hydrotalcite deacidifying agent: After dispersing and mixing phosphate-intercalated magnesium aluminum hydrotalcite, silane coupling agent KH-550 and 75% ethanol solution, nano titanium dioxide particles are added. After ultrasonic dispersion, centrifugation, washing and drying, composite hydrotalcite deacidifying agent is obtained. S3: Preparation of anti-PID composite filler: Surface modification of nano-tin oxide is performed using surfactant to obtain surface-modified nano-tin oxide. Barium metaphosphate dispersion, silane coupling agent KH-550 and surface-modified nano-tin oxide are mixed and dispersed, and then centrifuged, washed and dried to obtain anti-PID composite filler. S4: Aminolation modification of anti-PID composite packing: anti-PID composite packing, N,N-dimethylformamide, ethylenediamine and ammonia water with a mass fraction of 30% are mixed, heated and stirred in a water bath, condensed and refluxed, filtered to collect filter residue, washed and dried to obtain aminolated anti-PID composite packing. S5: Preparation of EVA film for acid-removing solar cells: EVA resin, main crosslinking agent, co-crosslinking agent, aminated anti-PID composite filler, composite hydrotalcite acid remover, lubricant, ultraviolet absorber, light stabilizer, antioxidant and coupling agent are melt-blended, and then extruded, cast, cooled and shaped and wound to obtain EVA film for acid-removing solar cells.

[0009] Further, step S1: preparation of phosphate-intercalated magnesium aluminum hydrotalcite, specifically includes the following steps: S1.1: Add magnesium nitrate hexahydrate and aluminum nitrate nonahydrate to deionized water, stir to dissolve, and prepare Mg 2+ Concentration of 1.5–2.5 mol / L, Al 3+ For solution A with a concentration of 0.5–1.5 mol / L, sodium hydroxide is added to deionized water, stirred until dissolved, and then OH is prepared. - For solution B with a concentration of 1.5–4 mol / L, phosphate is added to deionized water, stirred, and dissolved to prepare PO4. 3- Solution C has a concentration of 0.2–1 mol / L; S1.2: Pour solution C into the reactor. Under a nitrogen atmosphere, while stirring, slowly add solutions A and B dropwise into the reactor at a rate of 2 mL / min. When the volume ratio of the added solutions A and B to the solution C in the reactor is (1-1.2):1:1, the dropwise addition operation is completed. Stir the reaction for 1-2 hours. Adjust the pH of the mixed solution in the reactor to 6-8 with a 1 mol / L sodium hydroxide solution. React at 70-80℃ for 12-48 hours. S1.3: After the treatment is completed and the mixture has cooled naturally, the collected gel is washed 2 to 5 times with deionized water, and then dried at 40 to 60°C for 12 to 24 hours to obtain phosphate-intercalated magnesium aluminum hydrotalcite.

[0010] Furthermore, in step S1.1, the phosphate is sodium phosphate or potassium phosphate.

[0011] Further, step S2: preparation of the composite hydrotalcite acid-removing agent specifically includes the following steps: S2.1: Add 5-20 parts by weight of phosphate-intercalated magnesium aluminum hydrotalcite and 10-30 parts by weight of silane coupling agent KH-550 to 70-120 parts by weight of 75% ethanol solution, and ultrasonically disperse for 20-30 minutes to obtain a dispersion. S2.2: Add 1-14 parts by weight of nano-titanium dioxide particles to the dispersion, ultrasonically disperse at 40-60℃ for 20-30 min, then centrifuge, wash with deionized water 2-3 times, and dry at 70-80℃ for 4-8 h to obtain composite hydrotalcite deacidifying agent.

[0012] Further, step S3: preparation of anti-PID composite filler, specifically includes the following steps: S3.1: Add nano-tin oxide to deionized water and ultrasonically disperse for 5-10 min to prepare a nano-tin oxide dispersion with a mass fraction of 2-5%. Add a surfactant to the nano-tin oxide dispersion, wherein the amount of surfactant added is 1-3% of the mass of the nano-tin oxide dispersion, and the surfactant is hexadecyltrimethylammonium bromide. Stir magnetically for 20-40 min, then ultrasonically disperse for 10-30 min. Subsequently, after filtration, washing and drying, surface-modified nano-tin oxide is obtained. S3.2: Add barium metaphosphate to deionized water and ultrasonically disperse for 5-10 min to prepare a barium metaphosphate dispersion with a mass fraction of 4-8%. Add silane coupling agent KH-550 to the barium metaphosphate dispersion and ultrasonically disperse for 20-40 min. Then, add surface-modified nano-tin oxide, heat to 50-80℃, and ultrasonically disperse for 40-90 min. After centrifugation, washing, and drying, the anti-PID composite filler is obtained.

[0013] Furthermore, in step S3.2, the mixing mass ratio of the surface-modified nano-tin oxide, silane coupling agent KH-550, and barium metaphosphate dispersion is (1-6):(21-35):(90-130).

[0014] Further, step S4: Amination modification of the anti-PID composite filler, specifically includes the following steps: S4.1: Add 1-12 parts by weight of anti-PID composite packing to 100-160 parts by weight of N,N-dimethylformamide, stir evenly, then add 20-45 parts by weight of ethylenediamine and 6-16 parts by weight of ammonia water with a mass fraction of 30%, stir and mix for 40-60 minutes, then continue stirring in a water bath at 45-60℃ for 20-40 minutes, and then reflux using a reflux condenser for 4-6 hours. Filter the mixture obtained after reflux and collect the filter residue. S4.2: The filter residue is washed with anhydrous ethanol 3 to 5 times to remove excess ethylenediamine. The product obtained after washing is dried at 50 to 60°C for 6 to 12 hours to obtain the aminated anti-PID composite packing.

[0015] The present invention has the following advantages: 1. In this invention, by inserting phosphate ions into the interlayer of magnesium aluminum hydrotalcite, not only can the interlayer spacing of magnesium aluminum hydrotalcite be increased, thus improving its ion exchange capacity, but the charge density between the layers can also be increased, enhancing its ability to adsorb anions and improving the efficiency of the ion exchange process. This is beneficial for the adsorption of acetic acid released from the EVA membrane. At the same time, by loading nano-titanium dioxide particles onto the surface of phosphate-intercalated magnesium aluminum hydrotalcite, the prepared composite hydrotalcite acid remover can effectively increase the specific surface area of ​​phosphate-intercalated magnesium aluminum hydrotalcite due to the addition of nano-titanium dioxide particles, providing more adsorption sites and further enhancing the adsorption and capture effect of acetic acid. This makes the composite hydrotalcite acid remover more effective in treating acetic acid, achieving the purpose of effective acid reduction and removal. 2. In this invention, by loading nano-tin oxide onto the surface of barium metaphosphate, the anti-PID composite filler is added to the EVA film for acid-removing solar cells, which is beneficial to improving the mechanical properties of the EVA film for acid-removing solar cells. Furthermore, the interfacial effect between nano-tin oxide and barium metaphosphate in the anti-PID composite filler is beneficial to forming a charge transport microenvironment that captures and releases ions, preventing the migration and diffusion of metal ions in the glass layer, reducing the damage caused by charge accumulation, effectively suppressing the abnormal movement of charge carriers, and improving the anti-PID capability of the EVA film for acid-removing solar cells. 3. In this invention, by amylating the anti-PID composite filler, the interaction between the anti-PID composite filler and the EVA resin is enhanced, and the compatibility between the anti-PID composite filler and the EVA resin is improved. This further improves the mechanical properties and durability of the EVA film for acid-free solar cells. Furthermore, the amino structure on the aminated anti-PID composite filler is alkaline, which can capture and neutralize free acetic acid in the EVA film for acid-free solar cells, thereby reducing the content of free acetic acid in the EVA film for acid-free solar cells, further playing a role in acid reduction and removal, and improving the aging resistance of the EVA film for acid-free solar cells. Attached Figure Description

[0016] Figure 1 This is a flowchart illustrating the preparation method of the EVA film for acid-free solar cells in an embodiment of the present invention. Detailed Implementation

[0017] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0018] Example 1 A method for preparing an EVA film for an acid-free solar cell, such as... Figure 1 As shown, the specific steps include: S1: Preparation of phosphate-intercalated magnesium aluminum hydrotalcite S1.1: Add magnesium nitrate hexahydrate and aluminum nitrate nonahydrate to deionized water, stir to dissolve, and prepare Mg 2+ Concentration of 2 mol / L, Al 3+ To prepare a 1 mol / L solution A, sodium hydroxide is added to deionized water and stirred until dissolved, thus preparing an OH solution. - To prepare PO4, sodium phosphate was added to deionized water and stirred until dissolved, resulting in a 4 mol / L solution B. 3- Solution C has a concentration of 1 mol / L; S1.2: Pour solution C into the reactor. Under a nitrogen atmosphere, while stirring, slowly add solutions A and B dropwise into the reactor at a rate of 2 mL / min. When the volume ratio of the added solutions A and B to the solution C in the reactor is 1:1:1, the dropwise addition operation is completed. Stir the reaction for 2 hours. Adjust the pH of the mixed solution in the reactor to 7 with a 1 mol / L sodium hydroxide solution. React at 80°C for 24 hours. S1.3: After the treatment is completed and the mixture has cooled naturally, the obtained gel is collected, washed 5 times with deionized water, and then dried at 50°C for 24 hours to obtain phosphate-intercalated magnesium aluminum hydrotalcite. S2: Preparation of composite hydrotalcite acid remover S2.1: Add 20 parts by weight of phosphate-intercalated magnesium aluminum hydrotalcite and 30 parts by weight of silane coupling agent KH-550 to 120 parts by weight of 75% ethanol solution, and ultrasonically disperse for 30 min to obtain a dispersion. S2.2: 14 parts by weight of nano titanium dioxide particles were added to the dispersion and ultrasonically dispersed at 60°C for 30 min. After centrifugation and washing with deionized water three times, the mixture was dried at 75°C for 8 h to obtain the composite hydrotalcite deacidifying agent. S3: Preparation of anti-PID composite filler S3.1: Add nano-tin oxide to deionized water and ultrasonically disperse for 10 min to prepare a nano-tin oxide dispersion with a mass fraction of 5%. Add hexadecyltrimethylammonium bromide to the nano-tin oxide dispersion, with the amount of hexadecyltrimethylammonium bromide added being 3% of the mass of the nano-tin oxide dispersion. Stir magnetically for 40 min, then ultrasonically disperse for 30 min. Subsequently, after filtration, washing and drying, surface-modified nano-tin oxide is obtained. S3.2: Barium metaphosphate was added to deionized water and ultrasonically dispersed for 10 min to prepare a 5% barium metaphosphate dispersion. Silane coupling agent KH-550 was added to the barium metaphosphate dispersion and ultrasonically dispersed for 40 min. Subsequently, surface-modified nano-tin oxide was added, with the mixing mass ratio of surface-modified nano-tin oxide, silane coupling agent KH-550, and barium metaphosphate dispersion being 6:35:120. The mixture was heated to 80℃ and ultrasonically dispersed for 90 min. After centrifugation, washing, and drying, the anti-PID composite filler was obtained. S4: Anti-PID composite filler amylation modification S4.1: Add 12 parts by weight of anti-PID composite packing to 160 parts by weight of N,N-dimethylformamide, stir evenly, then add 45 parts by weight of ethylenediamine and 16 parts by weight of ammonia water with a mass fraction of 30%, stir and mix for 60 min, then continue stirring in a 60℃ water bath for 40 min, then reflux using a reflux condenser for 6 h, filter the mixture obtained after reflux and collect the filter residue; S4.2: The filter residue was washed 5 times with anhydrous ethanol to remove excess ethylenediamine. The product obtained after washing was dried at 60°C for 12 hours to obtain the aminated anti-PID composite packing. S5: Preparation of EVA film for acid-free solar cells 95 parts of EVA resin with a VA content of 28% and a melt index of 25 g / 10 min, 4 parts of tert-butyl peroxide, 0.5 parts of triallyl isocyanate, 3.2 parts of aminated anti-PID composite filler, 1.8 parts of composite hydrotalcite deacidifying agent, 1.5 parts of stearamide, 1 part of 2,4-dihydroxybenzophenone, 1 part of sebacic acid bis-2,2,6,6-tetramethylpiperidinol ester, 1 part of antioxidant 1010 and 0.5 parts of silane coupling agent KH-550 were added to an extruder for melt blending to obtain a mixture. Subsequently, the mixture was extruded, cast, cooled and shaped and wound to obtain an acid-removing type EVA film for solar cells.

[0019] Example 2 A method for preparing an EVA film for an acid-free solar cell, such as... Figure 1 As shown, the specific steps include: S1: Preparation of phosphate-intercalated magnesium aluminum hydrotalcite S1.1: Add magnesium nitrate hexahydrate and aluminum nitrate nonahydrate to deionized water, stir to dissolve, and prepare Mg 2+ Concentration of 2 mol / L, Al 3+ To prepare a 1 mol / L solution A, sodium hydroxide is added to deionized water and stirred until dissolved, thus preparing an OH solution. - To prepare PO4, sodium phosphate was added to deionized water and stirred until dissolved, resulting in a 4 mol / L solution B. 3- Solution C has a concentration of 1 mol / L; S1.2: Pour solution C into the reactor. Under a nitrogen atmosphere, slowly add solutions A and B dropwise into the reactor while stirring. The dropwise addition rate of solutions A and B is 2 mL / min. When the volume ratio of solutions A and B to solution C in the reactor is 1:1:1, the dropwise addition operation is completed. Stir the reaction for 1 h. Adjust the pH of the mixed solution in the reactor to 7 with a 1 mol / L sodium hydroxide solution. React at 70 °C for 48 h. S1.3: After the treatment is completed and the mixture has cooled naturally, the obtained gel is collected, washed 5 times with deionized water, and then dried at 40°C for 24 hours to obtain phosphate-intercalated magnesium aluminum hydrotalcite. S2: Preparation of composite hydrotalcite acid remover S2.1: Add 20 parts by weight of phosphate-intercalated magnesium aluminum hydrotalcite and 30 parts by weight of silane coupling agent KH-550 to 120 parts by weight of 75% ethanol solution, and ultrasonically disperse for 20 min to obtain a dispersion. S2.2: 14 parts by weight of nano-titanium dioxide particles were added to the dispersion and ultrasonically dispersed at 40℃ for 20 min. After centrifugation and washing with deionized water three times, the mixture was dried at 80℃ for 4 h to obtain the composite hydrotalcite deacidifying agent. S3: Preparation of anti-PID composite filler S3.1: Add nano-tin oxide to deionized water and ultrasonically disperse for 5 min to prepare a nano-tin oxide dispersion with a mass fraction of 5%. Add hexadecyltrimethylammonium bromide to the nano-tin oxide dispersion, with the amount of hexadecyltrimethylammonium bromide added being 3% of the mass of the nano-tin oxide dispersion. Stir magnetically for 20 min, then ultrasonically disperse for 20 min. Subsequently, after filtration, washing and drying, surface-modified nano-tin oxide is obtained. S3.2: Barium metaphosphate was added to deionized water and ultrasonically dispersed for 5 min to prepare a 5% (w / w) barium metaphosphate dispersion. Silane coupling agent KH-550 was added to the barium metaphosphate dispersion and ultrasonically dispersed for 20 min. Then, surface-modified nano-tin oxide was added, wherein the mixing mass ratio of surface-modified nano-tin oxide, silane coupling agent KH-550 and barium metaphosphate dispersion was 6:35:120. The temperature was raised to 60℃ and ultrasonically dispersed for 60 min. Subsequently, after centrifugation, washing and drying, the anti-PID composite filler was obtained. S4: Anti-PID composite filler amylation modification S4.1: Add 12 parts by weight of anti-PID composite packing to 160 parts by weight of N,N-dimethylformamide, stir evenly, then add 45 parts by weight of ethylenediamine and 16 parts by weight of ammonia water with a mass fraction of 30%, stir and mix for 40 min, then continue stirring in a 45℃ water bath for 40 min, then reflux using a reflux condenser for 4 h, filter the mixture obtained after reflux and collect the filter residue; S4.2: The filter residue was washed 5 times with anhydrous ethanol to remove excess ethylenediamine. The product obtained after washing was dried at 50°C for 10 hours to obtain the aminated anti-PID composite packing. S5: Preparation of EVA film for acid-free solar cells 95 parts of EVA resin with a VA content of 28% and a melt index of 25 g / 10 min, 4 parts of tert-butyl peroxide, 0.5 parts of triallyl isocyanate, 3.2 parts of aminated anti-PID composite filler, 1.8 parts of composite hydrotalcite deacidifying agent, 1.5 parts of stearamide, 1 part of 2,4-dihydroxybenzophenone, 1 part of sebacic acid bis-2,2,6,6-tetramethylpiperidinol ester, 1 part of antioxidant 1010 and 0.5 parts of silane coupling agent KH-550 were added to an extruder for melt blending to obtain a mixture. Subsequently, the mixture was extruded, cast, cooled and shaped and wound to obtain an acid-removing type EVA film for solar cells.

[0020] Example 3 A method for preparing an EVA film for an acid-free solar cell, such as... Figure 1 As shown, the specific steps include: S1: Preparation of phosphate-intercalated magnesium aluminum hydrotalcite S1.1: Add magnesium nitrate hexahydrate and aluminum nitrate nonahydrate to deionized water, stir to dissolve, and prepare Mg 2+ Concentration of 2 mol / L, Al 3+ To prepare a 1 mol / L solution A, sodium hydroxide is added to deionized water and stirred until dissolved, thus preparing an OH solution. - To prepare PO4, sodium phosphate was added to deionized water and stirred until dissolved, resulting in a 4 mol / L solution B. 3- Solution C has a concentration of 0.5 mol / L; S1.2: Pour solution C into the reactor. Under a nitrogen atmosphere, while stirring, slowly add solutions A and B dropwise into the reactor at a rate of 2 mL / min. When the volume ratio of the added solutions A and B to the solution C in the reactor is 1.2:1:1, the dropwise addition operation is completed. Stir the reaction for 2 hours. Adjust the pH of the mixed solution in the reactor to 7 with a 1 mol / L sodium hydroxide solution and react at 80℃ for 24 hours. S1.3: After the treatment is completed and the mixture has cooled naturally, the obtained gel is collected, washed 5 times with deionized water, and then dried at 50°C for 24 hours to obtain phosphate-intercalated magnesium aluminum hydrotalcite. S2: Preparation of composite hydrotalcite acid remover S2.1: Add 5 parts by weight of phosphate-intercalated magnesium aluminum hydrotalcite and 10 parts by weight of silane coupling agent KH-550 to 70 parts by weight of 75% ethanol solution, and ultrasonically disperse for 30 min to obtain a dispersion. S2.2: Two parts by weight of nano-titanium dioxide particles were added to the dispersion and ultrasonically dispersed at 60°C for 30 min. After centrifugation and washing with deionized water three times, the mixture was dried at 75°C for 8 h to obtain the composite hydrotalcite deacidifying agent. S3: Preparation of anti-PID composite filler S3.1: Add nano-tin oxide to deionized water and ultrasonically disperse for 10 min to prepare a nano-tin oxide dispersion with a mass fraction of 3%. Add hexadecyltrimethylammonium bromide to the nano-tin oxide dispersion, with the amount of hexadecyltrimethylammonium bromide added being 3% of the mass of the nano-tin oxide dispersion. Stir magnetically for 40 min, then ultrasonically disperse for 30 min. Subsequently, after filtration, washing and drying, surface-modified nano-tin oxide is obtained. S3.2: Barium metaphosphate was added to deionized water and ultrasonically dispersed for 10 min to prepare a barium metaphosphate dispersion with a mass fraction of 8%. Silane coupling agent KH-550 was added to the barium metaphosphate dispersion and ultrasonically dispersed for 40 min. Subsequently, surface-modified nano-tin oxide was added, wherein the mixing mass ratio of surface-modified nano-tin oxide, silane coupling agent KH-550, and barium metaphosphate dispersion was 4:25:100. The temperature was raised to 80℃ and ultrasonically dispersed for 90 min. After centrifugation, washing, and drying, the anti-PID composite filler was obtained. S4: Anti-PID composite filler amylation modification S4.1: Add 5 parts by weight of anti-PID composite filler to 100 parts by weight of N,N-dimethylformamide, stir evenly, then add 30 parts by weight of ethylenediamine and 10 parts by weight of ammonia water with a mass fraction of 30%, stir and mix for 60 min, then continue stirring in a 60℃ water bath for 40 min, then reflux using a reflux condenser for 6 h, filter the mixture obtained after reflux and collect the filter residue; S4.2: The filter residue was washed 5 times with anhydrous ethanol to remove excess ethylenediamine. The product obtained after washing was dried at 60°C for 12 hours to obtain the aminated anti-PID composite packing. S5: Preparation of EVA film for acid-free solar cells 95 parts of EVA resin with a VA content of 28% and a melt index of 25 g / 10 min, 4 parts of tert-butyl peroxide, 0.5 parts of triallyl isocyanate, 3.2 parts of aminated anti-PID composite filler, 1.8 parts of composite hydrotalcite deacidifying agent, 1.5 parts of stearamide, 1 part of 2,4-dihydroxybenzophenone, 1 part of sebacic acid bis-2,2,6,6-tetramethylpiperidinol ester, 1 part of antioxidant 1010 and 0.5 parts of silane coupling agent KH-550 were added to an extruder for melt blending to obtain a mixture. Subsequently, the mixture was extruded, cast, cooled and shaped and wound to obtain an acid-removing type EVA film for solar cells.

[0021] Comparative Example 1 Compared with Example 1, the difference of Comparative Example 1 is that step S2 is removed, and the composite hydrotalcite deacidifying agent in step S5 is replaced with an equal weight of the phosphate intercalated magnesium aluminum hydrotalcite obtained in step S1.3. The remaining steps remain unchanged, and an EVA film for deacidified solar cells is prepared. This is referred to as Comparative Example 1.

[0022] Comparative Example 2 Compared with Example 1, Comparative Example 2 differs in that sodium phosphate in step S1.1 is replaced with sodium carbonate, and sodium carbonate is added to deionized water, stirred and dissolved to prepare CO3. 2-Solution D with a concentration of 1 mol / L was used to replace solution C in step S1.2 to prepare carbonate-intercalated magnesium aluminum hydrotalcite. Then, phosphate-intercalated magnesium aluminum hydrotalcite in step S2.1 was replaced with carbonate-intercalated magnesium aluminum hydrotalcite, while the other steps remained unchanged, to prepare an EVA film for acid-free solar cells. This was designated as Comparative Example 2.

[0023] Comparative Example 3 Compared with Example 1, Comparative Example 3 differs in that steps S1.2-S1.3 are removed, and solution B from step S1.1 is poured into the reactor. Under a nitrogen atmosphere, solution A is slowly added dropwise to the reactor while stirring. The dropwise addition rate of solution A is 2 mL / min. When the volume ratio of solution A to solution B in the reactor is 1:1, the dropwise addition operation ends. The reaction is stirred for 2 hours, and the pH value of the mixed solution in the reactor is adjusted to 7 with a 1 mol / L sodium hydroxide solution. The reaction is carried out at 80°C for 24 hours. After the treatment is completed and the mixture is naturally cooled, the resulting gel is collected, washed 5 times with deionized water, and then dried at 50°C for 24 hours to obtain nitrate-intercalated magnesium aluminum hydrotalcite. The phosphate-intercalated magnesium aluminum hydrotalcite in step S2.1 is replaced with nitrate-intercalated magnesium aluminum hydrotalcite, while the other steps remain unchanged. An EVA film for acid-free solar cells is prepared and designated as Comparative Example 3.

[0024] Comparative Example 4 Compared with Example 1, the difference of Comparative Example 4 is that step S4 is removed, and the aminated anti-PID composite filler in step S5 is replaced with an equal weight of the anti-PID composite filler obtained in step S3.2. The remaining steps remain unchanged, and an EVA film for deacidified solar cells is prepared. This is referred to as Comparative Example 4.

[0025] Comparative Example 5 Compared with Example 1, the difference of Comparative Example 5 is that steps S3-S4 are removed, and the aminated anti-PID composite filler in step S5 is replaced with an equal weight of a mixed filler composed of nano-tin oxide and barium metaphosphate in a mass ratio of 1:1. The remaining steps are unchanged, and an EVA film for deacidified solar cells is prepared. This is referred to as Comparative Example 5.

[0026] Performance testing: (1) Power Attenuation Performance: The EVA films used in the deacidified solar cells of Examples 1-3 and Comparative Examples 1-5 were assembled into photovoltaic modules using the same polycrystalline silicon cells, glass, and backsheets. The photovoltaic modules assembled using the deacidified EVA films of Examples 1-3 and Comparative Examples 1-5 were tested according to IEC TS 62804-1 "Test Method for Voltage-Induced Attenuation Detection of Photovoltaic Modules". The test conditions were as follows: temperature 85℃, relative humidity 90%, and test time 240h. The power attenuation of the photovoltaic modules before and after the test was measured. The test results are shown in Table 1. (2) Mechanical properties: The tensile strength and elongation at break of the EVA films used in the deacidified solar cells of Examples 1-3 and Comparative Examples 1-5 were tested according to GB / T29848-2018. The test results are shown in Table 2; (3) Damp heat aging test: Damp heat aging tests were conducted on the EVA films used in the acid-free solar cells of Examples 1-3 and Comparative Examples 1-5. The test conditions were as follows: temperature 85℃, relative humidity 85%, and test time 1000h. Using a Fourier transform infrared spectrometer, the peak area of ​​the carbonyl group in the carboxyl group of the EVA film used in the acid-free solar cells before and after the test was detected, and the peak area ratio P of the carbonyl group in the carboxyl group before and after the test was calculated. The formula for calculating the ratio P is: P = (1760cm² after the test) / (1760cm² after the test) -1 :-C=O free acetic acid) / before the experiment (1760cm) -1 The free acid content of the EVA film used in deacidified solar cells was inferred by the presence of -C=O free acetic acid. The transmittance of the EVA film before and after the test was measured according to GB / T29848-2018, and the transmittance retention rate was calculated. The formula for the transmittance retention rate is: Transmittance retention rate = (Transmittance after test / Transmittance before test) * 100%. The yellowing index (△YI) before and after the test was measured according to GB2409. The test results are shown in Table 3.

[0027] Table 1. Power attenuation performance results of photovoltaic modules assembled with EVA films from acid-removing solar cells in the examples and comparative examples.

[0028] Table 2 Mechanical property results of EVA films for deacidified solar cells in the examples and comparative examples.

[0029] Table 3. Results of Damp-Heat Aging Resistance of EVA Films for Acid-Deprived Solar Cells in Examples and Comparative Examples

[0030] As shown in Tables 1-2, after power attenuation performance and mechanical performance testing, the photovoltaic modules assembled from the EVA films for deacidified solar cells in Examples 1-3 all exhibited power attenuation rates ≥2%. The tensile strength and elongation at break of the EVA films for deacidified solar cells in Examples 1-3 were also superior to those in Comparative Examples 1-5. This indicates that the addition of composite hydrotalcite deacidifying agent and aminated anti-PID composite filler can improve the anti-PID performance of the EVA film for deacidified solar cells and also help improve the mechanical properties of the EVA film for deacidified solar cells. Secondly, as shown in Table 3, after the damp heat aging test, the amount of free acid in the EVA film of the acid-removing solar cell in Examples 1-3 was significantly less than that in Comparative Examples 1-3. The test results of transmittance retention and yellowing index change were also better than those in Comparative Examples 1-3. This indicates that the composite hydrotalcite acid remover has excellent adsorption performance for acetic acid and good aging resistance. The free acid content in the EVA film of the acid-removing solar cell in Comparative Examples 4-5 was between that in Examples 1-3 and Comparative Examples 1-3. The test results of transmittance retention and yellowing index change were worse than those in Examples 1-3. This indicates that the aminated anti-PID composite filler also has a certain acid removal function, which can reduce the acetic acid content in the EVA film of the acid-removing solar cell and also help improve the aging resistance of the EVA film of the acid-removing solar cell.

[0031] It should be understood that those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims. Parts not described in detail in this specification are prior art known to those skilled in the art.

Claims

1. An acid-removing EVA film for solar cells, characterized in that: By weight, it includes the following raw materials: 86-95 parts of EVA resin, 1.8-4 parts of main cross-linking agent, 0.1-0.5 parts of auxiliary cross-linking agent, 1.3-3.2 parts of amino anti-PID composite filler, 0.1-1.8 parts of composite hydrotalcite acid scavenger, 0.1-1.5 parts of lubricant, 0.04-1 parts of ultraviolet absorber, 0.01-1 parts of light stabilizer, 0.1-1 parts of antioxidant and 0.1-0.5 parts of coupling agent; The raw materials for preparing the composite hydrotalcite acid scavenger include: 5 to 20 parts of phosphate intercalated magnesium aluminum hydrotalcite, 1 to 14 parts of nano titanium dioxide particles, 10 to 30 parts of silane coupling agent KH-550 and 70 to 120 parts of 75% by mass ethanol solution, wherein the phosphate intercalated magnesium aluminum hydrotalcite is a layered composite material formed by inserting phosphate ions between magnesium aluminum hydrotalcite layers; The raw materials for preparing the amination anti-PID composite filler include: 1 to 12 parts of the anti-PID composite filler, 100 to 160 parts of N, N-dimethylformamide, 20 to 45 parts of ethylenediamine and 6 to 16 parts of 30% ammonia water by mass; The raw materials for preparing the anti-PID composite filler include: surface-modified nano-tin oxide, silane coupling agent KH-550 and barium metaphosphate dispersion, wherein the mixing mass ratio of the surface-modified nano-tin oxide, silane coupling agent KH-550 and barium metaphosphate dispersion is (1-6): (21-35): (90-130), the surface-modified nano-tin oxide is nano-tin oxide modified by a surfactant, and the mass fraction of the barium metaphosphate dispersion is 4-8%.

2. The acid-removing solar cell EVA film according to claim 1, characterized in that: The VA content of EVA resin is 28-33%, and the melt index is 25-43 g / 10 min.

3. The acid-removing solar cell EVA film according to claim 2, characterized in that: The main cross-linking agent is at least one of tert-butyl peroxycarbonate-2-ethylhexyl, tert-amyl peroxy (2-ethylhexyl) carbonate, tert-butyl peroxyacetate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxybenzoate or diisopropylbenzene peroxide; the auxiliary cross-linking agent is at least one of triallyl isocyanurate, triallyl cyanurate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, propoxylated trimethylolpropane triacrylate, propoxylated neopentyl glycol diacrylate, and ethoxylated trimethylolpropane triacrylate; the lubricant is one or more of stearic acid, calcium stearate, zinc stearate, butyl stearate, stearamide, and oleamide; the ultraviolet absorber is phenyl o-hydroxybenzoate, 2-(2'-hydroxy- The invention discloses a novel light stabilizer comprising at least one of bis-2,2,6,6-tetramethylpiperidinol sebacate, N,N,-bis-(2,2,6,6-tetramethyl-4-piperidinyl)-1,6-hexanediamine and 2,4-dichloro-6-(4-morpholinyl)-1,3,5-triazine; a coupling agent comprising at least one of silane coupling agent KH-570, silane coupling agent KH-560, silane coupling agent KH-670 and silane coupling agent KH-550; and an antioxidant comprising at least one of antioxidant 1010 and antioxidant 168.

4. A method for preparing the acid-removing EVA film for solar cells according to claim 3, characterized in that: The steps include: S1: Preparation of phosphate intercalated magnesium aluminum hydrotalcite, using magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and phosphate as raw materials, sodium hydroxide as a precipitant, deionized water as a solvent, preparing a solution, titrating coprecipitation, hydrothermal treatment, washing and drying to obtain phosphate intercalated magnesium aluminum hydrotalcite; S2: Preparation of composite hydrotalcite acid scavenger: after dispersing and mixing phosphate intercalated magnesium aluminum hydrotalcite, silane coupling agent KH-550 and 75% ethanol solution by mass, nano-titanium dioxide particles were added, and the composite hydrotalcite acid scavenger was obtained after ultrasonic dispersion, centrifugal separation, washing and drying; S3: Preparation of anti-PID composite filler: surface modification of nano-tin oxide is performed using a surfactant to obtain surface-modified nano-tin oxide, and barium metaphosphate dispersion, silane coupling agent KH-550 and surface-modified nano-tin oxide are mixed and dispersed, and then centrifuged, washed and dried to obtain an anti-PID composite filler; S4: Amination modification of the anti-PID composite filler, wherein the anti-PID composite filler, N,N-dimethylformamide, ethylenediamine and 30% ammonia water are mixed, and the mixture is heated and stirred in a water bath, condensed and refluxed, filtered to obtain the residue, washed and dried to obtain the amination anti-PID composite filler; S5: Preparation of EVA film for acid-removing solar cells, EVA resin, main cross-linking agent, auxiliary cross-linking agent, amino anti-PID composite filler, composite hydrotalcite acid scavenger, lubricant, ultraviolet absorber, light stabilizer, antioxidant and coupling agent are melt-blended, and then extruded, cast, cooled and formed, and rolled up to obtain the EVA film for acid-removing solar cells.

5. The method for preparing the acid-removing solar cell EVA film according to claim 4, wherein: Step S1: Preparation of phosphate intercalated magnesium aluminum hydrotalcite, specifically comprising the following steps: S1.1: Add magnesium nitrate hexahydrate and aluminum nitrate nonahydrate into deionized water, stir and dissolve to form Mg 2+ The concentration is 1.5~2.5mol / L, Al 3+ Solution A with a concentration of 0.5 to 1.5 mol / L, add sodium hydroxide to deionized water, stir to dissolve, and prepare OH - Solution B with a concentration of 1.5 to 4 mol / L, add phosphate to deionized water, stir to dissolve, and prepare PO4 3- Solution C with a concentration of 0.2 to 1 mol / L; S1.2: Pour solution C into the reactor, and slowly drop solution A and solution B into the reactor while stirring under a nitrogen atmosphere. The dropping speed of solution A and solution B is 2 mL / min. When the volume ratio of the dropped solution A and solution B to the solution C in the reactor is (1-1.2):1:1, the dropping operation is completed. Stir the reaction for 1-2 hours, adjust the pH value of the mixed solution in the reactor to 6-8 with a sodium hydroxide solution with a concentration of 1 mol / L, and react at 70-80°C for 12-48 hours; S1.3: After the treatment is completed and the mixture is cooled naturally, the obtained colloid is collected, washed with deionized water for 2 to 5 times, and then dried at 40 to 60° C. for 12 to 24 hours to obtain phosphate-intercalated magnesium aluminum hydrotalcite.

6. The method for preparing the acid-removing solar cell EVA film according to claim 5, wherein: In step S1.1, the phosphate is sodium phosphate or potassium phosphate.

7. The method for preparing the acid-removing solar cell EVA film according to claim 6, wherein: Step S2: Preparation of composite hydrotalcite acid scavenger, specifically comprising the following steps: S2.1: Add 5 to 20 parts by weight of phosphate-intercalated magnesium aluminum hydrotalcite and 10 to 30 parts by weight of silane coupling agent KH-550 to 70 to 120 parts by weight of 75% ethanol solution, and ultrasonically disperse for 20 to 30 minutes to obtain a dispersion; S2.2: Add 1 to 14 parts by weight of nano titanium dioxide particles to the dispersion, and ultrasonically disperse at 40 to 60° C. for 20 to 30 minutes. Subsequently, centrifuge and wash with deionized water for 2 to 3 times, and dry at 70 to 80° C. for 4 to 8 hours to obtain a composite hydrotalcite acid scavenger.

8. The method for preparing the acid-removing solar cell EVA film according to claim 7, wherein: Step S3: Preparation of anti-PID composite filler, specifically comprising the following steps: S3.1: Add nano-tin oxide to deionized water, ultrasonically disperse for 5 to 10 minutes, and prepare a nano-tin oxide dispersion with a mass fraction of 2 to 5%. Add a surfactant to the nano-tin oxide dispersion, wherein the amount of the surfactant added is 1 to 3% of the mass of the nano-tin oxide dispersion, and the surfactant is hexadecyltrimethylammonium bromide. Stir magnetically for 20 to 40 minutes, and then ultrasonically disperse for 10 to 30 minutes. Then, filter, wash and dry to obtain the surface-modified nano-tin oxide. S3.2: Add barium metaphosphate to deionized water and ultrasonically disperse for 5 to 10 minutes to prepare a barium metaphosphate dispersion with a mass fraction of 4 to 8%. Add silane coupling agent KH-550 to the barium metaphosphate dispersion and ultrasonically disperse for 20 to 40 minutes. Then, add the surface-modified nano-tin oxide, heat to 50 to 80°C, and ultrasonically disperse for 40 to 90 minutes. Then, after centrifugation, washing and drying, an anti-PID composite filler is obtained.

9. The method for preparing the acid-removing solar cell EVA film according to claim 8, wherein: In step S3.2, the mixing mass ratio of the surface-modified nano-tin oxide, the silane coupling agent KH-550 and the barium metaphosphate dispersion is (1-6): (21-35): (90-130).

10. The method for preparing the acid-removing EVA film for solar cells according to claim 9, characterized in that: Step S4: Amination modification of the anti-PID composite filler, specifically comprising the following steps: S4.1: Add 1 to 12 parts by weight of anti-PID composite filler to 100 to 160 parts by weight of N,N-dimethylformamide, stir evenly, then add 20 to 45 parts by weight of ethylenediamine and 6 to 16 parts by weight of 30% ammonia water, stir and mix for 40 to 60 minutes, then continue stirring in a 45 to 60°C water bath for 20 to 40 minutes, then use a reflux condenser to condense and reflux for 4 to 6 hours, and filter the mixed solution obtained after condensation and reflux to obtain the filter residue; S4.2: The filter residue is washed with anhydrous ethanol for 3 to 5 times to remove excess ethylenediamine, and the product obtained after washing is dried at 50 to 60° C. for 6 to 12 hours to obtain an amino-anti-PID composite filler.

Citation Information

Patent Citations

  • Deacidification type EVA packaging adhesive film and preparation method thereof

    CN117866546A

  • Hydrolysis-resistant and PID-resistant EVA (Ethylene Vinyl Acetate) adhesive film for solar packaging material and preparation method thereof

    CN118185503A

  • Packaging adhesive film and preparation method and application thereof

    CN118599438A

  • Anti-aging deacidification type functional master batch and ultra-low acid EVA photovoltaic adhesive film prepared from anti-aging deacidification type functional master batch

    CN118620545A

  • Anti-corrosion packaging adhesive film and preparation method thereof

    CN118667477A

Cited By

  • High-strength and high-light-transmittance antireflection film and preparation method thereof

    CN120716274A